Phytochemistry and antioxidant activity of Lallemantia iberica aerial parts - N. Khosravi Dehaghi; A.R. Gohari; S.S. Sadat-Ebrahimi; H. Naghdi Badi; Y. Amanzadeh (Iranian Society of Pharmacognosy, 2016)
Background and objectives:Lallemantia iberica (Lamiaceae) is a medicinal plant distributed in different parts of Iran. This research, has evaluated the phytochemical constituents and antioxidant activity of the aerial parts of the plant. Methods: Different chromatographic methods such as column chromatographies using Silica gel (normal and reversed phases), Sephadex LH-20 and HPLC were used for isolation of the compounds from the ethyl acetate and methanol extract of L. iberica aerial parts. The structures of the isolated compounds were elucidated using 1H-NMR, 13C-NMR and EI-MS. Antioxidant activity of the extracts were also evaluated in DPPH and FRAP tests. Results: Two sterols,β-sitosterol acetate (1), β-sitosterol (2), one triterpenoic acid,ursolic acid (3), one polyphenol, rosmarinic acid (4) and six flavonoides,Luteolin-7-O-glucoside (5), 4'-methoxy-luteolin-7-O-glucoside (6), apigenin-7-O-glucoside (7), Luteolin (8),  diosmetin (9), apigenin (10) were isolated and identified from the ethyl acetate and methanol extracts. The antioxidant activity of the ethyl acetate (IC50 189.95±2.8 μg/mL) and the methanol extracts (IC50 140±1.2 μg/mL) were compared to the standard antioxidant, BHA (IC50 100±1.6 μg/mL) in DPPH method. The reducing power of the ethyl acetate (300.28 μmol Eq FeSO4.7H2O/mg DW), the methanol extract (553.14 μmol Eq FeSO4.7H2O/mg DW) and BHA (558.36 μmol Eq FeSO4.7H2O/mg of standard) were elucidated in FRAP assay. Conclusion: The results introduce L. iberica as a medicinal plant with valuable constituents which are responsible of different pharmacological activities.